Educating Intuition: Reducing Risky Decisions Using Fuzzy-Trace Theory. (October 2015) - Reyna, Valerie F.; Weldon, Rebecca B.; McCormick, Michael
Risky decision making, especially in adolescence, is a major public health problem. However, fuzzy-trace theory suggests that bad outcomes are preventable by changing thinking and, therefore, feelings about risks. The theory aligns with new findings and has been shown to be effective in experiments on decreasing sexual risk taking, increasing medication adherence, and tailoring genetic testing. Despite the vulnerabilities of the adolescent brain, decision processes can be modified by applying evidence-based theory.